KEBIJAKAN PENEGAKAN HUKUM PIDANA DALAM MENANGGULANGI PERJUDIAN - Ahmad Burhan Hakim; Ida Arodatul Jannah (Program Studi Hukum Tata Negara dan diterbitkan oleh Program Studi Hukum Tata Negara dan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2023)
Criminal law is often used to solve social problems, especially in crime prevention. In particular, the problem of gambling as a form of social disease, a form of social pathology. Enforcement of criminal law to tackle gambling as deviant behavior must continue to be carried out. This is very reasonable because gambling is a threat a real threat to social norms that can lead to individual tensions as well as social tensions. Gambling is a real or potential threat to the nation. Thus gambling can become an obstacle to national development with material-spiritual aspects. Because gambling educates people to make a living in an unreasonable manner and forming a